Concentration of Fibroblasts in the Vocal Fold of Elderly - Carneiro, Neemias S. [UNESP]; Pessin, Adriana B.B. [UNESP]; Rodrigues, Sergio A. [UNESP]; Pellizon, Claudia H. [UNESP]; Xavier, Claudia M. [UNESP]; Martins, Regina H.G. [UNESP] (Elsevier, 2022)
Objective: To study the concentration of fibroblasts in the vocal folds of elderly people. Material and Methods: The vocal folds of 13 cadavers were removed and divided into two age groups: Control group: n-5, 18-40 years; Elderly group: n-8, ≥75 years). The vocal folds were dissected and prepared for immunohistochemical analysis using the SA100 antibody to fibroblasts. The sites analyzed were maculae flavae and medial (or vibrating) portion of the vocal folds. The AVsoft program was used to count the cells. Results: A higher concentration of fibroblasts was identified in the maculae flavae of the larynx of young adults and in the medial portion of the vocal folds of the elderly. However, these results did not determine statistically significant differences, allowing us to conclude that there was no effect of age on the concentration of fibroblasts in the vocal folds. Conclusion: In the larynx of the elderly, the fibroblast population remains similar to the young adults, both in the maculae flavae and in the body of the vocal folds, possibly being responsible for the constant production of fibrous matrix in the lamina propria. Functional changes in these cells are probably more marked than quantitative ones.
Keywords: Aging voice; Fibroblasts; Immunohistchemical; Presbyphonia